2022
DOI: 10.21037/apm-21-3633
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual acuity between phacoemulsification and extracapsular cataract extraction: a systematic review and meta-analysis

Abstract: Background: Surgical treatment is the primary intervention for cataracts. Extracapsular cataract extraction (ECCE) is a routine surgery for cataracts, phacoemulsification (PE) is another procedure with a small incision and injury area. This study investigated the comparison of the effects of these two procedures on the patient's visual acuity.Methods: Embase, PubMed, Cochrane Library, and SpringerLink databases were searched from January 2000 to August 2021 to obtain randomized controlled trial (RCT) studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…technique has been shown to be effective in treating cataracts and improving vision compared to other surgical techniques. 10,11,12 Based on research by Gogate et al and Pramita et al, improvement of vision with phacoemulsification will appear mainly around 6 weeks after phacoemulsification. This supports the results of the study because the time spam of when most patients achieve normal vision (≥ 6/12) is about 1 to 3 months after surgery.…”
Section: Prasad Et Al Filho Et Al and LI Et Al Explained That The Pha...mentioning
confidence: 99%
“…technique has been shown to be effective in treating cataracts and improving vision compared to other surgical techniques. 10,11,12 Based on research by Gogate et al and Pramita et al, improvement of vision with phacoemulsification will appear mainly around 6 weeks after phacoemulsification. This supports the results of the study because the time spam of when most patients achieve normal vision (≥ 6/12) is about 1 to 3 months after surgery.…”
Section: Prasad Et Al Filho Et Al and LI Et Al Explained That The Pha...mentioning
confidence: 99%
“…Moreover, it lessens the likelihood of anterior chamber absence or flatness, which typically follows trabeculectomy surgery alone. The previous meta-analysis discovered that combined surgery had a significantly greater IOP lowering effect than cataract surgery alone and was comparable with trabeculectomy alone [ 6 , 7 , 19 ]. In terms of two different combined surgeries, MSICS-trabeculectomy and phacotrabeculectomy, our findings revealed no significant difference in postoperative IOP between them.…”
Section: Reviewmentioning
confidence: 99%
“…Previous studies showed combined surgery provides better outcomes in visual acuity than two-stage surgery and fewer AGM needed postoperatively than phacoemulsification only [ 6 , 7 ]. The studies involved in this analysis showed a tremendous visual acuity improvement after both surgery groups.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Phacoemulsification is currently considered as the gold standard surgical option for treatment of cataract [1]. Although most cataract cases can be treated with phacoemulsification, cataracts that are too hard to be emulsified by phacoemulsification are occasionally needed extracapsular cataract extraction surgery [2]. The cataractous lens fragments are emulsified by the means of ultrasonic power used in phacoemulsification machines.…”
Section: Introductionmentioning
confidence: 99%